Establishment of postal audit system in intensity-modulated radiotherapy by radiophotoluminescent glass dosimeters and a radiochromic film. (April 2018) - Okamoto, Hiroyuki; Minemura, Toshiyuki; Nakamura, Mitsuhiro; Mizuno, Hideyuki; Tohyama, Naoki; Nishio, Teiji; Wakita, Akihisa; Nakamura, Satoshi; Nishioka, Shie; Iijima, Kotaro; Fujiyama, Daisuke; Itami, Jun; et al.
Graphical abstract: Highlights: This study is the first report to justify glass dosimetry for IMRT audit. The audit phantom was sent to 24 institutions to assess delivered dose. Glass dosimetry was reliable with a high measurement accuracy. Our postal audit system was established without relaxing criterion. Our system provides a high-level criterion of 3%/3 mm using glass dosimetry. Abstract: We developed an efficient postal audit system to independently assess the delivered dose using radiophotoluminescent glass dosimeters (RPLDs) and the positional differences of fields using EBT3 film at the axial plane for intensity-modulated radiotherapy (IMRT). The audit phantom had a C-shaped target structure as a planning target volume (PTV) with four measurement points for the RPLDs and a cylindrical structure as the organ at risk (OAR) for one measurement point. The phantoms were sent to 24 institutions. Point dose measurements with a 0.6 cm 3 PTW farmer chamber were also performed to justify glass dosimetry in IMRT. The measured dose with the RPLDs was compared to the calculated dose in the institution's treatment planning system (TPS). The mean ± 1.96σ of the ratio of the measured dose with the RPLDs to the farmer chamber was 0.997 ± 0.024 with no significant difference ( p  = .175). The investigations demonstrated that glass dosimetry was reliable with a high measurement accuracy comparable to the chamber. The mean ± 1.96σ for the dose differences with a reference of the TPS dose for the PTV and the OAR was 0.1 ± 2.5% and −2.1 ± 17.8%, respectively. The mean ± 1.96σ for the right-left and the anterior–posterior direction was −0.9 ± 2.8 and 0.5 ± 1.4 mm, respectively. This study is the first report to justify glass dosimetry for implementation in IMRT audit in Japan. We demonstrate that our postal audit system has high accuracy with a high-level criterion of 3%/3 mm.